Intergenerational Earnings Persistence and Economic Inequality in the Long-Run: Evidence from French Cohorts, 1931-1975 - Arnaud Lefranc (Institute of Labor Economics (IZA), 2018)
This paper analyzes long-term trends in intergenerational earnings persistence in France for male cohorts born between 1931 and 1975. This time period has witnessed important changes in the French labor market and educational system, in particular an important compression of earnings differentials as well as a large expansion in access to secondary and higher education. Using a two-sample instrumental variables approach, I estimate two measures of intergenerational economic persistence: the intergenerational earnings elasticity (IGE) and the intergenerational correlation (IGC). Over the period, the IGE exhibits a V-shaped pattern. It falls from a high of value of .6 for cohorts born in the 1930s to around .4 for those born in the 1950s, but subsequently rises to a level close to the beginning of the period. In contrast, the IGC remains relatively stable over the period. This suggests that changes in the IGE are partly driven by transitory responses to changes in cross-sectional inequality rather than long-term changes in the degree of intergenerational persistence.
Keywords: D1; D3; J3; 330; intergenerational mobility; intergenerational persistence; earnings; inequality; trends; elasticity; corre-lation; education; France